Role of regional policies in promoting networking and innovation activity of firms - Kirsi Mukkala; Jari Ritsilä (European Regional Science Association (ERSA), 2004)
The success of firms and regions is increasingly defined by their innovation and learning capabilities. It has been emphasized in several studies that a local operational environment may have a positive impact on innovation activity of firms. From policy point of view, the relationship between firms and their local environment is an important research topic. The purpose of this paper is to explore whether there is a demand for regional policy makers in promoting innovative and networking activity of firms, and what are the appropriate strategies in this regard. The concept of innovative milieu provides a theoretical base for this study. The data used is based on personal interviews representing 30 high tech firms located in Jyväskylä Science Park in Finland. The results show that the firms appreciate an individual-level approach by policy makers which enables them to take the real needs of firms into consideration. A developed service structure, that is planned to meet the demand of new and established firms as well as possible, is an essential part of the well functioning operational environment. Supporting contacts with service providers and experts from different fields and organizing collective meetings for firms are important targets for the policy makers. In the innovation process, a commercial view of external part is considered very crucial. The small advances which alternate between the development of the innovation process and networks among firms and their interest groups could form a favourable path towards an operational environment with efficient innovative networks.
Keywords: 330